(untitled) (Journal of Engineering Studies and Research, 2023)
This paper explores and elucidates the concept of Cryptocurrency. It contributes a framework of digital money and also provides an analysis of the price range, which influences Cryptocurrency volume and market capitalisation. Findings from the OLS analysis show that the low price genre influences the volume and market capitalization of Cryptocurreny. Based on the results, the paper develops a price, volume and market capitalization framework for Cryptocurrency. The findings provide a practical and conceptual contribution for investors and future researchers on the concept of digital currency.